Exploring The Prophetic Values Contained In The Advocate Profession - Muhammad Nurcholis Alhadi; Khudzaifah Dimyati; Absori Absori; Kelik Wardiono (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The advocate profession in the early Islamic treasury is not formally institutionalized so that it needs to explore prophetic values in the history of Islamic civilization and objectified into the advocate profession. This study aims to reveal the advocate profession from the perspective of prophetic science and trace prophetic values into the foundation of the advocate profession. This study uses a normative research model through library materials or literature literature as a written source. The results of the study show, first, Islam respects human rights in defending their interests in court. Islam guarantees justice in a trial, equality of rights, and guarantees the right to defend the rights both alone and through legal counsel in accordance with the wakalah system. Second, prophetic values as the foundation of the advocate profession are upholding justice, being a peacemaker, the concept of submitting affairs to the experts leave the matter to the expert / knowledgeable, the concept of mutual help, and advocate ethics. These values are not only human dimensions but also transcendental.